Digital Wood Design Innovative Techniques of Representation in Architectural Design - Bianconi, Fabio; Filippucci, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book explores various digital representation strategies that could change the future of wooden architectures by blending tradition and innovation. Composed of 61 chapters, written by 153 authors hailing from 5 continents, 24 countries and 69 research centers, it addresses advanced digital modeling, with a particular focus on solutions involving generative models and dynamic value, inherent to the relation between knowing how to draw and how to build. Thanks to the potential of computing, areas like parametric design and digital manufacturing are opening exciting new avenues for the future of construction. The book's chapters are divided into five sections that connect digital wood design to integrated approaches and generative design; to model synthesis and morphological comprehension; to lessons learned from nature and material explorations; to constructive wisdom and implementation-related challenges; and to parametric transfigurations and morphological optimizations. .
Integrated approach and generative design -- Centrality of representation as a synthesis model and morphological comprehension -- Connection between Nature lessons and material explorations -- Constructive wisdom and realization challenges -- Parametric transfigurations and morphological optimizations.
Keywords: Buildings -- Design and construction; Biogeography; Sustainable architecture; Computer-aided engineering; Building Construction and Design; Biogeosciences; Sustainable Architecture/Green Buildings; Computer-Aided Engineering (CAD, CAE) and Design